Rising burden of Diabetes-Public Health Challenges & way out - Kakkar, Rakesh (Nepal Journal of Epidemiology, 2016)
Secondary prevention by community physician can be provided at PHC & CHC level. Focus should always be on early detection of diseases through screening programmes and prevention of mortality. Prevention of chronic morbidity and functional impairment should be emphasized more. At policy level advocacy should be done for providing essential medication like insulin available and affordable to all who need them. At tertiary level rehabilitation, disability limitation and palliative care of person with NCDs is also needed.